2015
DOI: 10.1111/jcpp.12486
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol drinking in pregnancy increases risk for children's persistent conduct problems: causal effects in a Mendelian randomisation study

Abstract: BackgroundHeavy alcohol use during pregnancy can cause considerable developmental problems for children, but effects of light‐moderate drinking are uncertain. This study examined possible effects of moderate drinking in pregnancy on children's conduct problems using a Mendelian randomisation design to improve causal inference.MethodsA prospective cohort study (ALSPAC) followed children from their mother's pregnancy to age 13 years. Analyses were based on 3,544 children whose mothers self‐reported either not dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 45 publications
(74 reference statements)
1
32
2
1
Order By: Relevance
“…demonstrated a dose–response effect of prenatal alcohol exposure, for each of the three trimesters separately, on self‐reported behaviour problems in 22‐year‐old offsprings, after controlling for race, sex, maternal depression, hostility during pregnancy, prenatal marijuana exposure, prenatal tobacco exposure and the young adult's own substance use. Another recent study reported causal inference between moderate alcohol drinking (up to 6 units per week without binge drinking) in pregnancy and an increased risk for children's early‐onset‐persistent conduct problems . The negative psychological effects found in children exposed to moderate maternal alcohol consumption are summarized in Figure .…”
Section: Foetal Alcohol Spectrum Disordersmentioning
confidence: 98%
See 2 more Smart Citations
“…demonstrated a dose–response effect of prenatal alcohol exposure, for each of the three trimesters separately, on self‐reported behaviour problems in 22‐year‐old offsprings, after controlling for race, sex, maternal depression, hostility during pregnancy, prenatal marijuana exposure, prenatal tobacco exposure and the young adult's own substance use. Another recent study reported causal inference between moderate alcohol drinking (up to 6 units per week without binge drinking) in pregnancy and an increased risk for children's early‐onset‐persistent conduct problems . The negative psychological effects found in children exposed to moderate maternal alcohol consumption are summarized in Figure .…”
Section: Foetal Alcohol Spectrum Disordersmentioning
confidence: 98%
“…The literature of humans on genetic effects, alone and in an interaction with psychosocial factors, on vulnerability to behavioural problems and psychiatric disorders, is large. However, little is known about the contribution of genetic background of the offspring prenatally exposed to alcohol, and its interaction with environmental factors on the risk of development of FASD and subclinical traits …”
Section: Studies On Humans With Some Focus On the Serotonergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges of this approach are that some of the conditions for a valid IV are untestable, and weak instruments result in imprecise and sometimes inconsistent estimates . While there are some examples of IV analyses in perinatal epidemiology—several of them using Mendelian randomization—the approach has not been extensively explored in perinatal pharmacoepidemiology . In an attempt to validly estimate the effectiveness of antidepressants during pregnancy, Swanson et al evaluated preference‐based, calendar‐time–based, and geography‐based instruments, but concluded that they did not meet the required conditions for a valid analysis: Several of the tested instruments were weak, and all failed to provide better balance of measured covariates than the actual exposure status …”
Section: Confoundingmentioning
confidence: 99%
“…Some of these children will have been exposed in utero to chronic high levels of alcohol, the risks of which are well recognised 3 4. However, for others, alcohol exposure may have been moderate5 or at an occasional binge level,6 for which the risks are less clear. Data on the impact of maternal occasional binge drinking on the developing fetus are variable: the ALSPAC study in the UK reported developmental and learning problems (hyperactivity and inattention) associated with this exposure in 4-year-olds,7 while a Danish study found no impact on intelligence in 5-year olds 8.…”
Section: Introductionmentioning
confidence: 99%